I det VI kallar landet Sverige - från dräpande samtidssatir till nostalgisk dröm och mycket annat. Bilden av Sverige i Carl-Johan Vallgrens v isor - Żmuda-Trzebiatowska, Magdalena (Folia Scandinavica Posnaniensia, 2007)
Carl-Johan Vallgren, the writer and musician bom in 1964. has published eight books and released five records with his own lyrics and music. His novel called Den vidunderliga karlekens historia (The Horrific Sufferings of the Mind-Reading Monster Hercules Barefoot, His Wonderful Love and His Terrible Hatred) proved a spectacular success in 2002. The media describe him sometimes as „the least Swedish of all Swedish writers”. This opinion derives partly from his choice of the subjects and partly from the fact that Vallgren has travelled much in Asia and Europe and in the beginning of the 1990s he lived in Madrid and Copenhagen and then in Berlin for twelve years. This analysis of Vallgren’s lyrics is an attempt to show that the writer has never lost touch with his homeland to which he returned in 2005. His musical and literary stories paint a picture of Sweden with distinct features of social satire; Vallgren uses irony and black humour in a masterly manner, he shocks and even teeters on the edge of good taste. Nevertheless, drastic features are juxtaposed by lyrical threads and the note of nostalgia in his descriptions of characters, places and phenomena moderates Vallgren’s severe criticism.